Topical Antioxidant Potential of Telang Flower Extract (Clitoria ternatea L.) on IL-6 and VEGF Regulation in UV-B Exposure: An In Vivo Experimental Study (Gema Lingkungan Kesehatan, 2025)
UVB radiation can penetrate the epidermis and can induce DNA damage in skin cells by increasing ROS concentrations. Apart from that, UVB radiation also increases melanocyte proliferation which can cause melasma. Skin damage due to UV exposure is caused by the generation of  ROS and various inflammatory factors. Telang flowers contain Glutathione, which is one of the main antioxidants in the body, which has a skin depigmentation function. One of the physiological effects of glutathione is to inhibit melanogenesis by suppressing tyrosinase activity. Experimental research with post test control group. Groups KN, P1 and P2 were each exposed to UVB at 302 nm with a MED of 160 mJ/cm2, while group K0 was a healthy group. P1 was given 5% butterfly pea flower gel and P2 was given 10% gel every day for 14 days, while KN received base gel. On the 21st day, the tissue was analyzed for IL-6 and VEGF level using ELISA. There was a significant difference in the mean levels of IL-6 between the four groups, with the One Way Anova test p = 0.000 (p